2022
DOI: 10.1111/andr.13238
|View full text |Cite
|
Sign up to set email alerts
|

Identifying neuroimaging biomarkers for psychogenic erectile dysfunction by fusing multi‐level brain information: A resting‐state functional magnetic resonance imaging study

Abstract: Background: Psychogenic erectile dysfunction (pED) patients who are under their 40s in China consist of a major component of erectile dysfunction. Existing neuroimaging studies have demonstrated that pED is a functional disorder with aberrant neural representations on the local level, the regional level, and the global level, respectively. Therefore, it is reasonable to incorporate brain information from all these levels simultaneously into consideration when identifying neuroimaging biomarkers for pED.However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…The orbitofrontal cortex (ORB) and IFG are thought to mediate the sexual inhibition, especially cognitive sexual inhibition, together with the DLPFC, PCC, and other brain regions ( Cheng et al, 2015 ; Chen et al, 2017 ). Studies found that the abnormal patterns brain activity in the IFG of PED patients was likely to be related to dysfunction of sensorimotor function ( Zhang X. et al, 2022 ). A previous study showed that the lesions in the ORB or frontal cortex often lead to impairments in socio-affective regulation including sexual inhibition ( Baird et al, 2007 ; Cohen and Lieberman, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The orbitofrontal cortex (ORB) and IFG are thought to mediate the sexual inhibition, especially cognitive sexual inhibition, together with the DLPFC, PCC, and other brain regions ( Cheng et al, 2015 ; Chen et al, 2017 ). Studies found that the abnormal patterns brain activity in the IFG of PED patients was likely to be related to dysfunction of sensorimotor function ( Zhang X. et al, 2022 ). A previous study showed that the lesions in the ORB or frontal cortex often lead to impairments in socio-affective regulation including sexual inhibition ( Baird et al, 2007 ; Cohen and Lieberman, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, our previous study included patients with different types of ED, and the mechanism of action of acupuncture for psychogenic ED remains unclear. Currently, many studies tend to explore the mechanism of pED from the perspective of brain structure and function [ 35 ]. pED patients may have a structural damage to the brain, such as reduced white and gray matter, as well as dysfunctions in multiple regions of the brain [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sexual pleasure in the appropriate context could lead to excitation and higher arousal, which finally culminated ejaculation and this sexual pleasure disappeared immediately after ejaculation ( Georgiadis and Kringelbach, 2012 ). The brain was found to be strongly correlated with subjective sexual pleasure and the amount of sexual pleasure sufficient to reach ejaculation might be regulated by the balance between sexual inhibitory and excitatory ( Georgiadis and Kringelbach, 2012 ; Zhao et al, 2015 ; Wang et al, 2017 ; Jin et al, 2018 ; Zhang et al, 2022 ). Normal sexual function was the consequence of the balance between central neural inhibitory and excitatory mechanisms ( Rodriguez et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%